Implications of αvβ3 Integrin Signaling in the Regulation of Ca2+ Waves and Myogenic Tone in Cerebral Arteries. Issue 12 (December 2015) - Mufti, Rania E.; Zechariah, Anil; Sancho, Maria; Mazumdar, Neil; Brett, Suzanne E.; Welsh, Donald G.
Abstract : Objective—: The myogenic response is central to blood flow regulation in the brain. Its induction is tied to elevated cytosolic [Ca 2+ ], a response primarily driven by voltage-gated Ca 2+ channels and secondarily by Ca 2+ wave production. Although the signaling events leading to the former are well studied, those driving Ca 2+ waves remain uncertain. Approach and Results—: We postulated that αv β3 integrin signaling is integral to the generation of pressure-induced Ca 2+ waves and cerebral arterial tone. This hypothesis was tested in rat cerebral arteries using the synergistic strengths of pressure myography, rapid Ca 2+ imaging, and Western blot analysis. GRGDSP, a peptide that preferentially blocks αv β3 integrin, attenuated myogenic tone, indicating the modest role for sarcoplasmic reticulum Ca 2+ release in myogenic tone generation. The RGD peptide was subsequently shown to impair Ca 2+ wave generation and myosin light chain 20 (MLC20 ) phosphorylation, the latter of which was attributed to the modulation of MLC kinase and MLC phosphatase via MYPT1-T855 phosphorylation. Subsequent experiments revealed that elevated pressure enhanced phospholipase Cγ1 phosphorylation in an RGD-dependent manner and that phospholipase C inhibition attenuated Ca 2+ wave generation. Direct inhibition of inositol 1, 4, 5-triphosphate receptors also impaired Ca 2+ wave generation, myogenic tone, and MLC20 phosphorylation, partly through the T-855 phosphorylation site of MYPT1. Conclusions—: Our investigation reveals a hitherto unknown role for αv β3 integrin as a cerebral arterial pressure sensor. The membrane receptor facilitates Ca 2+ wave generation through a signaling cascade, involving phospholipase Cγ1, inositol 1, 3, 4 triphosphate production, and inositol 1, 4, 5-triphosphate receptor activation. These discrete asynchronous Ca 2+ events facilitate MLC20 phosphorylation and, in part, myogenic tone by influencing both MLC kinase and MLC phosphatase activity. Abstract : Supplemental Digital Content is available in the text.